Experience in the use of dendritic vaccines in the treatment of patients with recurrent gliomas - M. Yu. Rykov; I. S. Dolgopolov (Исследования и практика в медицине, 2022)
Purpose of the study. To substantiate the expediency of cellular immunotherapy in the treatment of patients with relapses of high-grade gliomas and evaluate the safety of injecting allogeneic cells directly into the cerebrospinal fluid.Materials and methods. Our study included 5 patients, median age 7,6 years (2–16). Three patients had anaplastic astrocytoma (AA) (1st recurrence – 1 patient, 2nd recurrence – 2 patients), 1 patient had glioblastoma multiforme (GBM) (3rd recurrence) and 1 had diffuse brainstem glioma (BSG). The median time to the first relapse was 12 months (4 to 16), to the second one was 5 months (1 to 8). The protocol of immunotherapy included combined administration of autologous dendritic cell-based vaccine (DV) and repeated intrathecal/intraventricular injections of donor allogenic immunocompetent cells (alloIC) for at least 2 years.Results. Two of 3 patients with AA experienced a progression-free interval of 67 and 71 months One patient with 3rd GBM relapse is alive without any therapy 13.3 years after immunotherapy start. The median time of follow-up was 67 months with the 2‑years overall survival was 58 %. Two patients died from disease progression within 6 and 7 months from the start of immunotherapy. Over the period of treatment the patients received a median of 20 (8 to 60) alloIC injections and 18 (8 to 44) DV administrations. No serious side-effect was observed.Conclusion. Immunotherapy could be an attractive option for treating patients with high-grade malignant gliomas irresponsible to conventional therapy and is worthy of further investigation.